PENINGKATAN KEMAMPUAN MENGENAL HURUF HIJAIYAH MELALUI PEMBELAJARAN LANGSUNG BERMEDIA AUDIO VISUAL PADA ANAK TUNAGRAHITA SEDANG - ISTIANAH, (Jurnal Pendidikan Khusus, 2018)
Abstract. Mentally retardation made the children difficult to recognize Hijaiyah letters. To be able to recognize Hijaiyah letters, the children had to understand every single Hijaiyah letters. To solve the problem, the researcher applied direct learning with audiovisual media which had purpose to enhance the recognizing Hijaiyah letters ability from Alif till Jim to the middle mentally retardation children of class III in SLB Aisyiyah Tulangan Sidoarjo. The purpose of this research was to describe the enhancement of recognizing Hijaiyah letters ability through direct learning with audiovisual media to the middle mentally retardation children of class III in SLB Aisyiyah Tulangan Sidoarjo. The methods of data collection in this research were observation and test. The data, which had been collected, was analized to describe the enhancement of recognizing Hijaiyah letters ability to the middle mentally retardation children with audiovisual media by the steps of data reduction, data presentation, and data conclusion. This research was a class treatment research which consisted of 2 cycles in which each cycle was implemented 2 meetings. The research result indicated that the recognizing Hijaiyah letters ability of middle mentally retardation children of class III in SLB Aisyiyah Tulangan Sidoarjo in cycle I had 54.8% result in the average of cycle I and 79,1% in cycle II. So, there was 24,3% enhancement.   Keywords: Hijaiyah letters, direct learning, audiovisual media.